IA case of canine squamous cell carcinoma secondary to solar keratosis (actinic carcinoma in situ) - PAPADOGIANNAKIS, E; KONTOS, V (Journal of the Hellenic Veterinary Medical Society, 2018)
We present the case of a squamous cell carcinoma developed in a pre-existing solar keratosis of the trunk in a whitehaired Dogue Argentino. Deep pyoderma along with exfoliative erythroderma were the initial clinical findings. Several months after the diagnosis of solar keratosis, the dog presented with multiple nodules and ulcers on the flank and abdomen and the diagnosis of malignancy was confirmed microscopically.